2020
DOI: 10.1039/c9tb01755k
|View full text |Cite
|
Sign up to set email alerts
|

A chitosan modified asymmetric small-diameter vascular graft with anti-thrombotic and anti-bacterial functions for vascular tissue engineering

Abstract: Rapid endothelialization and prevention of restenosis are two vital challenges for the preparation of a small-diameter vascular graft (SDVG), while postoperative infection after implantation is often neglected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 76 publications
0
31
0
Order By: Relevance
“…For the scaffold fabrication, the electrospinning technology was utilized [127]. The results of this study showed that the PCL/Ch hybrid-based SDVGs have similar anti-thrombogenic properties as the heparin-coated vessel conduits, while the bacterial killing ratios were 64% for S. aureus and 73% E. coli [127]. Yao et al [129] also developed electrospun PCL/Ch SDVGs, which were further combined with heparin and referred as Hep-PC/Ch grafts.…”
Section: Biopolymersmentioning
confidence: 88%
See 3 more Smart Citations
“…For the scaffold fabrication, the electrospinning technology was utilized [127]. The results of this study showed that the PCL/Ch hybrid-based SDVGs have similar anti-thrombogenic properties as the heparin-coated vessel conduits, while the bacterial killing ratios were 64% for S. aureus and 73% E. coli [127]. Yao et al [129] also developed electrospun PCL/Ch SDVGs, which were further combined with heparin and referred as Hep-PC/Ch grafts.…”
Section: Biopolymersmentioning
confidence: 88%
“…The production of vascular grafts made of chitosan has also been reported [127]. Chitosan is a linear polysaccharide that is closely related to sulfated glycosaminoglycans (sGAGs) [128].…”
Section: Biopolymersmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 Tissue engineering scaffolds may effectively overcome the above defects. 7 In order to promote cell adhesion, migration, proliferation and mimic the extracellular matrix (ECM) 8 of native nanofibers and avoid side effects such as chronic inflammation and complement cascade initiation, 9 it is crucial to choose of appropriate materials when fabrication the tissue engineering scaffolds. [10][11][12][13] An ideal biomaterial for tissue engineering scaffolds should present excellent biocompatibility.…”
Section: Introductionmentioning
confidence: 99%